Peningkatan Hasil Belajar Siswa Kelas V SDN 011 Pulau Kedundung pada Mata Pelajaran IPA dengan Materi Sifat-Sifat Cahaya melalui Metode Percobaan - Rayanis, Rayanis (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2017)
The research was motivated by the findings on Science learning process about light properties where there were only 50% students who passed the minimal mastery score. To improve the score, the experiment method was applied. The objective of this research was to improve students’ learning result in SD N 011 Pulau Kedundung grade V. This research was based on four steps of Classroom Action Research; planning, proceeding, observing, and reflecting. It was done in two cycles. The result of the research showed there was significant improvement in cycle 1 that 80% students passed the score and in cycle 2, 100% students passed. It can be concluded that the use of experiment method could improve students’ learning result SD N 011 Pulau Kedundung grade V in Science learning about light properties.